Possible Association of HLA-DR and DQ Molecules with Autoimmune Hepatitis in Iraqi Patients - AL-Obeidy, Eman Sh.; Mousawy, Khalida M.; AL-Akayshi, Raghad J H; Abdalelah, Laith (Journal of the Faculty of Medicine Baghdad, 2010)
Background: Human leukocyte antigen (HLA) is the most polymorphic genetic system in man. The genes of this region seem to influence susceptibility to certain diseases. Patients and methods: Polymerase chain reaction-Sequence Specific Primers PCR-SSP is the method used to asses HLA-typing of 100 blood samples of 60 AIH patients and 40 healthy normal controls. Results: An increased frequency of HLA-DR3, DR4 and DR7 was observed for patients group versus control group with P-value (0.0001, 0.05, and 0.001) respectively, while DR*0211 (DR2) may be formed the basis for protection against the disease. HLA-DQ on the other hand, yielded on association in Iraqi patients with AIH. Conclusions: This finding demonstrated that HLA-DR3, DR4 and DR7 might play a role in AIH susceptibility.